The Effect of Health Education Video Based on Islamic Purification Jurisprudence on Handwashing Intention - Nurmeilis; Nurrika, Dieta; Anggraeni, Yuni; Alkaff, Raihana Nadra; Sukmayanti, Zanastia (Universitas Nahdlatul Ulama Surabaya, 2023)
This study aimed to determine the effectiveness of health education videos based on Islamic purification fiqh on students’ intention to wash their hands using and buying clay soap by applying the theory of planned behavior. A two-armed pre-post intervention was conducted in Banten from February to August 2022. Participants were randomly assigned to an intervention or a control group. The total sample of this research is 187 respondents. This study found that the intention to wash hands using clay soap before and after the short video educational media intervention increased by 4.3%, and the intention to buy it increased by 4.8%. In the three variables that construct the intention to wash hands using clay soap, only the subjective norm variable is related to the behavioural intention to use clay soap. Religious reasons have the potential to increase handwashing behaviour using clay soap. Short video educational media interventions targeting Generation Z can be carried out to increase the intention to practice handwashing.